2021
DOI: 10.2147/ndt.s297460
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Psychological Distress and Associated Factors among Hospitalized Patients During the COVID-19 Pandemic at Selected Hospitals in Southwest Ethiopia

Abstract: Background: The aim of this study was to assess the prevalence of psychological distress and associated factors among hospitalized patients during the COVID-19 pandemic at three selected hospitals in southwest Ethiopia. Methods: An institution-based cross-sectional study design was conducted among hospitalized patients during the COVID-19 pandemic at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The high rates of anxiety and depression observed within our group of patients align with the results reported in studies from other countries, such as Ethiopia and China, which documented comparable levels of anxiety and depression linked to hospital isolation during the first phase of the pandemic [ 30 , 31 ]. In Morocco, an online survey conducted among the general population during the outbreak yielded similar results, with 49% and 53% of respondents reporting anxiety and depression, respectively [ 15 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The high rates of anxiety and depression observed within our group of patients align with the results reported in studies from other countries, such as Ethiopia and China, which documented comparable levels of anxiety and depression linked to hospital isolation during the first phase of the pandemic [ 30 , 31 ]. In Morocco, an online survey conducted among the general population during the outbreak yielded similar results, with 49% and 53% of respondents reporting anxiety and depression, respectively [ 15 ].…”
Section: Discussionsupporting
confidence: 89%
“…This can be explained by past experiences of health adversities, leading to an increased perception of life threat. A cross-sectional study in Ethiopia further illustrates this, revealing that hospitalized COVID-19 patients with medium and high perceived life threat were three and five times more likely to have psychological distress [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with Gudmundsson et al (2006) [45] who concluded that COPD women were more likely to suffer from more significant anxiety or depression. There could be more factors like more vulnerability to sociocultural factors associated with the mental impact, or more fluctuation in hormonal levels which are associated with emotional symptoms and make women more likely to report negative emotions than men [46,47].…”
Section: Discussionmentioning
confidence: 99%